Natural frequency of cancer cells as a starting point in cancer treatment - Jaganathan, Saravana Kumar (Indian Academy of Sciences, 2016)
Breast cancer and prostate cancer are the most common gender-specific types of cancer among women and men respectively, around the world. The most preferred treatment embraced by the patients is chemotherapy. The anticancer drugs developed and used so far cannot completely cure cancer at all stages and also exhibit some side effects in the patients who undergo chemotherapy. Besides this, some cancer cells eventually acquire resistance to many drugs and evade the treatment procedures. All these factors play a vital role in persuading the researches to find alternative modes of treatment for cancer. This communication proposes an unconventional mode of cancer treatment by determining the natural frequencies of normal and cancer cells. By utilizing these frequencies, it is possible to kill the cancer cells specifically, sparing the healthy cells. The normal and cancer cells in case of breast (MCF-10A, MCF-7) as well as prostate cancer (BPH, LNCap) are modelled as a sphere in ANSYS. The modal analysis is done in order to obtain their natural frequencies along with their mode shapes at different frequencies. The results show that the natural frequency of the normal cells is much higher than that of the cancer cells at each corresponding mode. The natural frequency is proportional to the mechanical properties of the cells and is insignificant with respect to the change in diameter of the cells. Thus, utilizing the natural frequency, cancer cells may be specifically targeted while the burdens of chemotherapy and drug resistance.